β-glucan as a Techno-Functional Ingredient in Dairy and Milk-Based Products — A review - Mykhalevych, Artur; Polishchuk, Galyna; Nassar, Khaled; Osmak (Fedchenko), Tetiana; Buniowska-Olejnik, Magdalena (My University, 2022)
The article systematizes information about the sources of -glucan, its technological functions and practical aspects of its use in dairy and milk-based products. According to the analysis of scientific information, the main characteristics of -glucan classifications were considered: the source of origin, chemical structure, and methods of obtention. It has been established that the most popular in the food technology of dairy products are -glucans from oat and barley cereal, which exhibit pronounced technological functions in the composition of dairy products (gel formation, high moisture-binding capacity, increased yield of finished products, formation of texture, and original sensory indicators). The expediency of using -glucan from yeast and mushrooms as a source of biologically active substances that ensure the functional orientation of the finished product has been revealed. For the first time, information on the use of -glucan of various origins in the most common groups of dairy and milk-based products has been systematized. The analytical review has scientific and practical significance for scientists and specialists in the field of food production, in particular dairy products of increased nutritional value. У статті систематизовано відомості про джерела отримання β-глюкану, його технологічні функції та практичні аспекти використання в молочних і молоковмісних продуктах. За результатами аналізу наукової інформації розглянуто основні характеристики класифікацій β-глюканів: за джерелом походження, хімічною будовою та способами отримання. Встановлено, що найбільш популярними в харчовій технології молочних продуктів є β-глюкани вівса та ячменю, які виявляють виражені технологічні функції у складі молочних продуктів (гелеутворення, висока вологозв'язуюча здатність, підвищення виходу готової продукції, формування текстури та оригінальні сенсорні показники). Обґрунтовано доцільність використання β-глюкану з дріжджів та грибів як джерела біологічно активних речовин, що забезпечують функціональну спрямованість готового продукту. Вперше систематизовано відомості про використання β-глюкану різного походження в найбільш поширених групах молочних і молоковмісних продуктах. Аналітичний огляд має наукове та практичне значення для науковців і спеціалістів у галузі виробництва харчових продуктів, зокрема молочних продуктів підвищеної харчової цінності.
Keywords: polysaccharides; microalgae; mushrooms; yeast; bioactive substances; ice cream; cheese; fermented milk products; milk drinks; β-glucan; кафедра технології молока і молочних продуктів; полісахариди; мікроводорості; гриби; дріжджі; біологічно активні речовини; морозиво; сир; кисломолочні продукти; молочні напої; β-глюкан